Mechanically robust all-polymer solar cells enabled by polymerized small molecule acceptors featuring flexible siloxane-spacers. Issue 38 (7th September 2022) - Lee, Jin-Woo; Lee, Sun-Woo; Kim, Jingwan; Ha, Yeon Hee; Sun, Cheng; Ngoc-Lan Phan, Tan; Lee, Seungjin; Wang, Cheng; Kim, Taek-Soo; Kim, Yun-Hi; Kim, Bumjoon J.
Abstract : New polymer acceptors (PYSiO- X ( X = 0–30%)) containing siloxane-based flexible spacers (SiO-FSs) are developed. The resulting halogen-free solvent processed all-polymer solar cells show high photovoltaic efficiency and mechanical robustness. Abstract : Robust mechanical properties and high power conversion efficiencies (PCEs) of all-polymer solar cells (all-PSCs) are both the prerequisites for their application in wearable and stretchable electronics. However, these properties typically encounter a trade-off relationship. Herein, we report the development of new polymerized small-molecule acceptors (PSMAs) containing siloxane (SiO)-based flexible spacers (FSs) and demonstrate high-performance and mechanically robust all-PSCs. The introduction of highly flexible SiO-FSs increases the mechanical ductility of all-PSCs. Importantly, the SiO-FS unit enhances the solubility of PSMAs, enabling the fabrication of high-performance all-PSCs by solution processing using a non-halogenated solvent. Therefore, a high PCE (13.5%) and crack-onset strain (COS = 15.2%) are achieved for the all-PSC based on a SiO-FS-containing PSMA (PYSiO-10), which are superior to those of the reference system without SiO-FS (PCE = 9.8% and COS = 9.6%).